MULTIPLE INTELLIGENCES AS PREDICTORS OF READING COMPREHENSION AND VOCABULARY KNOWLEDGE - Zarei, Abbas Ali; Afshar, Nima Shokri (Universitas Pendidikan Indonesia, 2014)
Abstract: The present study was conducted to investigate types of Multiple Intelligences as predictors of reading comprehension and vocabulary knowledge. To meet this objective, a 60-item TOEFL test and a 90-item multiple intelligences questionnaire were distributed among 240 male and female Iranians studying English at Qazali and Parsian Universities in Qazvin. Data were analyzed using a multiple regression procedure. The result of the data analysis indicated that musical, interpersonal, kinesthetic, and logical intelligences were predicators of reading comprehension. Moreover, musical, verbal, visual, kinesthetic and natural intelligences made significant contributions to predicting vocabulary knowledge. Â Key words: Multiple intelligences, reading comprehension, vocabulary knowledge.